A survey of clinical supervison by the principles as perceived by school teachers in Kuala Kangsar, Perak - Kamaruddin bin Yaakob
This study investigates the perceptions of teachers concerning their experiences in being observed ·by the principals with particular reference to public secondary schools in Kuala Kangsar district of Perak, Malaysia. This district is important to study because of the special program implemented by the state department of education for achievement of excellence in education. The population of this study consisted of 168 teachers in the public secondary schools in Kuala Kangsar. The instrument used for data collection was a close-ended , ritten questionnaire which comprised 25 items on the principals' roles in clinical supervision, organized into five categories: objectives, pre-observation conference, observations, post-observation conference and teachers perceptions of principal' s clinical supervision. The independent variables of gender, age, educational qualification and teaching experience were considered. The study attempts to see whether there are any significant differences between demographic variables in their effects on responses. The processes of clinical supervision such as principal objectives, pre-observation conference, observation and post-observation conferences form the major focus of the study. To supplement the analysis, the teachers perceptions on the capability of the principals have also been ascertained in the questionnaires and analysed. The study found that great majority of respondents indicated that thev did not feel embarrassed during their principal' s supervision. Onlv a minority of female teachers. especially the young and inexperienced ones. or those who were expecting to apply for prumotion showed fear While those \vith disciplinary problems with their classes were embarrassed. The more experienced and mature teachers felt confident.